ON THE JURISPRUDENCE OF WORKPLACE DISCRIMINATION - Racusen, Seth (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2019)
Brazilian anti-discrimination law has further complicated litigation against racial discrimination. During the thirty years under the antidiscrimination law of 1989 (7.716/89), racial discrimination complaints have been overwhelmingly treated as injúria, an injury to the honor of the complaining party and not racism, and after 1997 as injuria qualificada, a personal injury to the race of the individual. Under Brazilian legal classifications, injúria is a lesser charge than racism with lesser penalties that must be prosecuted by the individual and not the state. The designation of an allegation as injúria effectively curbed or denied a plaintiff’s ability to contest discriminatory treatment in the 1990’s. The unevenness and unwillingness of the Brazilian judiciary to apply the anti-discrimination law has been clearly documented. The judiciary tends to decontextualize allegations by evaluating them without recognition of the repercussions and social contexts of the alleged behavior.